CONSIDERAÇÕES DE ORDEM ENUNCIATIVA SOBRE A FORMAÇÃO DOS CÓDIGOS DE LINGUAGEM - Freixo, Estêvão (2020)
Researches in the field of linguistics that examines and describes the functioning of linguistic systems often relied on the assumption that a language corresponds to a system that prepares its users for the linguistic experience in the common space of the social universe. On the other hand, the developments of a language of enunciation have opened new horizons to the understanding of linguistic systems, as they pose the problem of dependency between the essential definition of a language and the existence of a corpus of stabilized utterances recognized as founders by a society. In this work, we selected some enunciative plans, through which we demonstrate some possibilities of contribution of the enunciative activity in the formation of the language codes. Among the various categories available, we have separated for the present work the classes of discursive genre, mode of enunciation, discursive practice and enunciative scene, as they appear in Dominique Maingueneau's theoretical developments in his discourse analysis work. We also reserved some space to discuss the relationship between the historicity of language and the mutability of the sign, where we articulate the Saussurean theory with the association established by Maingueneau between vocabulary and enunciative position.